Tensile properties of woven kenaf fiber reinforced polypropylene hybrid aluminium-composite - Mohd Zalani, Naziatul Fazilah; Dhar Malingam, Sivakumar; Selamat, Mohd Zulkefli (Asian Research Publishing Network (ARPN), 2016)
Concern on environmental impact of emission from the automobile and the uncertainties in fuel price has led to the development of lighter materials. Hybrid metal- composite is a sandwich structure which is lighter than its constituent monolithic metal. In this study, hybrid aluminium-composite (HAC) was fabricated using plain weave woven kenaf fiber reinforced polypropylene matrix composite sandwiched in between aluminium 6061-O using hot compression method. Tensile test was conducted on the HAC with two different fiber loading and fiber orientation. The fiber loading were with 1 mm pitch (X-type) and 5 mm pitch (Y-type) and the orientation were 0° and 45°. The result shows that tensile strength had been increased with the increment of fiber loading, where X-type tensile strength is higher than Y-type. Meanwhile, 45° fiber orientation gives higher tensile strength compared to 0°. The images of the fracture type experienced by the HAC after the tensile test was also observed.